ANALISIS SPILLOVER EFFECT INDEKS SAHAM GLOBAL TERHADAP INDEKS SAHAM SYARIAH DI INDONESIA SEBELUM, SAAT DAN PASCA COVID-19 - Cupian, Cupian; Annisa Noven, Sarah; Hibrizi, Emil (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to examine the spillover effect of the stock indexes of the United States, China, and Japan as the global benchmark stock indexes on the movement of the Islamic stock market in Indonesia in the period before, during, and after the Covid-19 pandemic crisis. The analysis model used is the Vector Autoregression (VAR) or Vector Error Correction Model (VECM) model to observe the spillover effect and Granger Causality Test to examine the causality among the variables. The results of this study indicate that both the New York Stock Exchange as a representation of the US stock index, the Shanghai Stock Exchange as a representation of the Chinese stock index, and the Nikkei 225 Index as a representation of the Japanese stock index have a spillover effect on the Jakarta Islamic Index in the period before, during, and after the Covid-19 pandemic crisis. In addition, the US, China, and Japan stock indexes have a causal relationship with the Indonesian Islamic stock market in the period before, during, and after the Covid-19 pandemic crisis.